Designing and Constructing Log Periodic Dipole Antenna to Monitor Solar Radio Burst: e-Callisto Space Weather - Hamidi, Z.S.; Ibrahim, Z.A.; Abidin, Z.Z.; Maulud, M.F.; Radzin, N.N.; Hamzan, N.; Anim, N.M.; Shariff, N.N.M. (IACSIT Press, 2012)
A Log Periodic Dipole Antenna (LPDA) for solar burst monitor in the range of (45 -870) MHz applications is presented. In this paper, we make an effort in designing a portable LPDA that suitable with the criteria, specification and practical enough although is the boom length size of the antenna is 5.45 meter. We choose value of 0.14 spacing factor τ= 0.8 as a directivity of antenna. This LPDA is constructed by using two (2) rod aluminums type with nineteenth (19) elements of different sizes. Some of suggestions on improving this design are also presented.